Pengaruh Perhatian Orang Tua, Konsep Diri Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Tentang Matematika Kelas Viii Smp Negeri Di Kecamatan Sausu Kabupaten Parigi Moutong - Sumiyati, Tri; Amri, Baso; Sukayasa, Sukayasa (Mitra Sains, 2017)
The research aimed at finding out and describing the direct and indirect effects of parents’ care, self-concept, and learning motivation toward the learning outcomes on mathematics. The population was all the students of Grade VIII of SMP Negeri in Sub-district of Sausu, Parigi Moutong Regency in 2013/2014. They were 201 students in 10 classes. The sample was 110 students in 5 classes taken by using simple random sampling technique. This research was ex-post facto with causality designed to explain the cause and effect relationship between the variables. The techniques of data collection consisted of questionnaire on parents’ care, self-concept, and learning motivation; and mathematics test. The data were analysed quantitatively by using line analysis with SPSS 20 and AMOS. It is found that: (1) parents’ care directtly contributed significantly to the students’ mathematics learning outcome; (2) the students’ self-concept directly contributed significantly to the students’ mathematics learning outcome; (3) parents’ care indirectly contributed significantly to the students’ learning outcome on mathematics through learning motivation; (4) the students’ self-concept indirectly contributed significantly to the students’ learning outcome on mathematics through learning motivation; (5) parents’ care, self-concept, and learning motivation directly and indirectly contributed significantly to the students’ learning outcomes on mathematics.